The Developing Liveworksheets in Teaching Grammar for EFL Students - Khoiriyah, Arum; Zuniati, Mai; A. Hashim, Umar Alfaruq; Suhono, Suhono; Irhamudin, Irhamudin; Hidayatullah, Rizky (International Journal on Advanced Science, Education, and Religion, 2024)
The aim of this research is to develop an electronic student worksheet using Live Worksheets for Grammar course to facilitate learning evaluation and to find out the improvement of student learning achievement in Grammar course. The research design used in this study was research & development method in producing e- worksheets. The ADDIE model was carried out to develop e-worksheet by following four procedures: Analysis, Design, Development, Implementation and Evaluation. This research was validated by material experts and design experts to get advice regarding the feasibility of e-worksheets in terms of media and materials. The sample of this research were 18 students were chosen as sample purposely because they had never used e-worksheets with the help of e-Liveworksheet. The data collected by using test and questionaire instruments delivered to the students. The results of this research showed that the validation results with an average score of 94% for Media validation and 85% for material validation, which means that the translated e-worksheet is included in the criteria for being very valid and suitable for use. The result of quesionaire of e-worksheets showed that the average student response is 85%, which means e-worksheets are positive and practical. Based on the post-test scores on learning outcomes, 18 of student respondents received complete post-test scores, the percentage is 66%. Thus, the use of e-worksheets improve students ability in studying Grammar. Thus, e-worksheet of GrammarI using Live Worksheets are valid, practical and effective.